Public administration and the overseas territories: what's a mother country to do? - Kent, James D. (1997)
The United States finds itself in the historically anomalous position of maintaining exclusive or shared sovereignty in a number of islands in the Pacific and the Caribbean. Their dependent political status imposes more than financial obligations on the United States. Although U.S. domestic resources are stretched thin, some modest steps can be taken to help the islands govern more effectively. These include continuing attempts to improve administration, developing new models of public administration, and clarifying and stabilizing the political status of the territories. - Reproduced
Keywords: Public administration